2022
DOI: 10.1177/00220426221076800
|View full text |Cite
|
Sign up to set email alerts
|

Medications for Opioid Use Disorder in the Criminal/Legal System: Knowledge, Beliefs, and Attitudes Among Rural Community-Based Stakeholders

Abstract: The aim of this study was to describe rural community stakeholders’ attitudes and perceptions of providing medication for opioid use disorder (MOUD) to individuals in the criminal/legal system. Data were utilized from a technical assistance initiative aimed at strengthening community-based OUD treatment within criminal/legal systems. A mixed-methods approach was applied. Survey responses were used to compare stakeholders’ who had and had not attended an MOUD training, and semistructured interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…For corrections staff, there is a need to emphasize the efficacy of buprenorphine. Current training leads to a decrease in beliefs about buprenorphine efficacy, which has also been found in another study 13 . While further research is needed to confirm the role of efficacy beliefs towards MOUD referral among correction staff, previous studies have found that the most effective trainings are those that break down abstinence‐oriented barriers that may limit a correctional employee's beliefs about the efficacy of evidence based MOUD 2,34 .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…For corrections staff, there is a need to emphasize the efficacy of buprenorphine. Current training leads to a decrease in beliefs about buprenorphine efficacy, which has also been found in another study 13 . While further research is needed to confirm the role of efficacy beliefs towards MOUD referral among correction staff, previous studies have found that the most effective trainings are those that break down abstinence‐oriented barriers that may limit a correctional employee's beliefs about the efficacy of evidence based MOUD 2,34 .…”
Section: Discussionsupporting
confidence: 59%
“…However, we believe this was the most appropriate ordering of data given the measures available and the fact that referral intention is still measured 12 months after training exposure. This study and others have found that trainings may be correlated with changing attitudes about buprenorphine in correctional settings 13 but the precise mechanisms of these trainings that have the greatest impact remains unknown. Friedmann et al 2 conducted a targeted intervention for the MATICCE study participants and found that a standardized, targeted training was effective at increasing positive beliefs about MOUD and increasing referral intentions.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations